Utilizing Local Waste: Sustainable Adsorption of Reactive Blue 235 on Surfactant-Modified Bamboo Fibers - Samriti Vaid; Varinder Kaur; Sanyog Sharma; Anupinder Singh; Bhavna Vaid; Raj Kumar Arya; G. D. Verros (Journal of Engineering)
In this research endeavor, we sought to enhance the efficacy of bamboo fibers through modification with the surfactant cetyltrimethylammonium bromide (CTAB) for the purpose of removing Reactive Blue 235 from effluent. Our investigation encompassed a comprehensive exploration of the impact of crucial parameters, namely, adsorbent dosage (0.25 g–1.25 g), contact time (10–80 min), pH (2–12), initial dye concentration (20–100 mg/L), and temperature (298 K, 308 K, and 318 K) on the dynamics of dye removal. The optimum dye removal efficiency of 94% for Reactive Blue 235 was obtained at an adsorbent dosage of 0.5 g/50 ml of dye solution, initial dye concentration of 40 mg/L, pH of 6, and contact time of 40 min. The experimental framework included the anticipation of data aligned with various isothermal and kinetic models, facilitating a nuanced understanding of the adsorption process. Our findings unveiled that the kinetics of adsorption adhered to a second-order model, while the Langmuir isotherm model aptly described the adsorption behavior. Particularly noteworthy was the monolayer’s adsorption capacity, quantified at an impressive 7.39 mg·g−1 at a temperature of 318 K. The value of Freundlich’s constant, KF, increases with an increase in temperature indicating the endothermic nature of adsorption. The magnitude of E obtained from Dubinin–Radushkevich isotherm varying from 3.92 to 4.66 kJ/mol on increasing temperature from 298 K to 318 K suggests that adsorption of RB235 on BAT is a physisorption (value of E is between 1 and 8 kJ/mol). Delving into the thermodynamic aspects of the process, we calculated ΔH and ΔS to be 54.88 kJ/mol and 184.54 J/mol/K, respectively. The consistently negative values of ΔG (between −0.183 kJ/mol and −3.884 kJ/mol) at all temperatures underscored the feasibility, spontaneity, and entropy-driven nature of the adsorption of RB235 on CTAB-treated bamboo fiber (BAT). What sets our study apart is the deliberate utilization of bamboo fibers sourced from local waste streams, embodying a commitment to sustainable practices. Beyond its effectiveness in effluent treatment, our approach aligns with eco-friendly principles by repurposing indigenous waste materials, contributing to a more sustainable and environmentally responsible future.